Fictions of the accident, accidents of fiction: tragedies of technology in Latin American (post) vanguard narrative (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article describes the dialogue between Latin American (post)vanguard narrative and the figure of the accident during the twentieth century. We propose a model of analysis that examines the assimilation of this socio-cultural phenomenon in terms of literary structure, reception and content. We propose a reading model based on the insightful contributions of Macedonio Fernandez's Museo de la Novela de la Eterna, and analyze the political-aesthetical figuration of the accident in a corpus of exemplary texts.
Keywords: Accident; Literary fiction; Macedonio Fernández; Tragedy; Technology